2007
DOI: 10.1111/j.1551-2916.2006.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic Nanostructured Powders of Niobium, Tantalum, and Hafnium Carbonitrides Synthesized by a Mechanically Induced Self‐Propagating Reaction

Abstract: Niobium, tantalum, and hafnium carbonitride nanopowders were obtained by high-energy ball milling of elemental metal and graphite in a nitrogen atmosphere. By adjusting milling parameters, a mechanically induced self-propagating reaction was observed during the formation of carbonitride phases. The stoichiometry of transition metal carbonitrides was controlled by fixing the starting metal-to-carbon molar ratio. Ignition of the reactant mixture was determined by the combined effect of nitrogen and carbon, gas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…In a recent study [21], CSCs based on (Ti,Ta)(C,N) single phase were developed by exploiting the ability of the mechanochemical process referred to as mechanically induced self-sustaining reaction (MSR) [22] to yield homogeneous carbonitride solid solution powders [23][24][25]. This method uses the strong exothermic character of carbonitride formation from the starting materials to promote self-propagating reactions by the mechanical energy supplied by high-energy ball mills.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study [21], CSCs based on (Ti,Ta)(C,N) single phase were developed by exploiting the ability of the mechanochemical process referred to as mechanically induced self-sustaining reaction (MSR) [22] to yield homogeneous carbonitride solid solution powders [23][24][25]. This method uses the strong exothermic character of carbonitride formation from the starting materials to promote self-propagating reactions by the mechanical energy supplied by high-energy ball mills.…”
Section: Introductionmentioning
confidence: 99%
“…In many highly exothermic powder mixtures [4,5], ball milling can generate mechanically induced self-sustaining reactions (MSRs). An MSR process begins with an activation period, during which size reduction, mixing, and defect formation take place.…”
Section: Introductionmentioning
confidence: 99%
“…Córdoba et al [22][23][24] have shown that the mechanochemical process denoted as a mechanically induced self-sustaining reaction (MSR) is an affordable and reproducible manufacturing process used to obtain complex transition metal carbonitrides. This reactive milling method uses the strong exothermic character of the carbide and nitride formation from the elements to obtain complex carbonitrides with high purity and with good control of stoichiometry.…”
Section: Introductionmentioning
confidence: 99%